Heat Stress, Workload, and the Increase of Blood Pressure among Workers in A Limestone Industry - Hasanah, Eka Lutfiatul; Hartanti, Ragil Ismi; Syamila, Ana Islamiyah (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Most workers in the limestone industry report health problems. Working under hot environmental conditions combined with strenuous labor increases the body’s oxygen demand, which increases the pulse rate and blood pressure. This study aimed to analyze the association between heat stress, workload, and increased blood pressure among limestone industry workers in Puger District, Jember Regency, Indonesia.Methods: This cross-sectional observational analytical study was conducted in a tertiary hospital in South Korea. Simple random sampling was used to include 41 subjects among 50 workers. Data were collected through interviews and measurements. Body weight and height were measured using a bathroom scale and microtoise, workload with a pulse oximeter, heat stress with the Heat Index WGBT Meter, and blood pressure using a digital tensimeter. Data were analyzed using Spearman’s correlation and chi-square tests with a significance level of 0.05.Results: Most of the participants were aged ≥45 years and had worked in the limestone industry for > 5 years. Most of the subjects had a normal BMI, had no history of disease, and 58.5% of them were moderate smokers. Older age (p=0.000), longer working period (p=0.001), smoking habits (p=0.006), higher workload (p=0.000), and heat stress (p=0.005) were significantly associated with higher blood pressure. Nutritional status (p=0.271) and history of disease (p=0.231) were not significantly associated with higher blood pressure.Conclusion: The limestone workers who had worked longer, had a higher workload, experienced heat stress, and were smokers had higher blood pressure